가상현실 기반 배관배선공사 교육훈련 콘텐츠 개발 및 평가 - 신정민(Jungmin Shin); 이석한(Seok-Han Lee); 김상연(Sang-Youn Kim); 정구철(Goo-Cheol Jeong) (디지털콘텐츠학회논문지, 2022)
본 논문에서는 머리착용 영상장치(HMD), 트래커를 포함한 가상현실컨트롤러, 그래픽렌더링, 햅틱렌더링링 모듈로 구성된 배관배선 공사를 위한 몰입형 훈련 시스템을 개발하였다. 또한 사용자 평가를 통해 직업훈련을 위한 학습 콘텐츠로서의 활용 가능성을 탐색하였다. 사용자 평가결과, 총 7개의 영역에 대한 사용자 만족도 평균은 5점만점에 3.98 (표준편차 : 0.69)로 대부분은 양호하게 측정되었으나 비교적 어려운 수행에서는 점수가 상대적으로 낮았다. 가상현실 기반의 직업훈련 콘텐츠에 관한 관심과 활용도가 증가하는 추세에 따라 실감형 콘텐츠 제작도 늘어나고 있으나, 각 훈련 분야별로 요구되는 훈련 효과의 내용은 다르며 이를 지원하는 가상현실 적용 방법도 훈련 분야 및 영역, 수행 특성별로 차이가 있다. 이를 위해 햅틱 피드백이 포함된 훈련의 난이도와 특성에 맞는 효과적인 몰입형 훈련콘텐츠가 다양하게 개발되어 확대·보급될 필요가 있다. In this study, we developed a virtual training system consisting of a head mounted display (HMD), a VR controller, a graphic rendering module, and a haptic rendering module for a plumbing and wiring training system, and furthermore we explored the applicability of the proposed system as learning content for vocational training. As a result, the mean scores of user experience in all 7 learning parts was 3.98 out of 5(standard deviation: 0.69), which was measured well in most cases, but the score was relatively low in difficult performance. It is expected that interest in virtual reality-based vocational training contents will increase in the future, and as the usage is expected to be diversified, the development of immersive education and training content will grow further. Therefore, it is necessary to develop various effective immersive training content suitable for the difficulty and characteristics of training that includes haptic feedback and expand its distribution. KCI Citation Count: 4